2016
DOI: 10.1007/s12182-016-0115-4
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary characteristics and processes of the Paleogene Dainan Formation in the Gaoyou Depression, North Jiangsu Basin, eastern China

Abstract: In this paper, the type, vertical evolution, and distribution pattern of sedimentary facies of the Paleogene Dainan Formation in the Gaoyou Depression of the North Jiangsu Basin are studied in detail. Results show that fan delta, delta, nearshore subaqueous fan, and lacustrine facies developed during the Dainan Formation period and their distribution pattern was mainly controlled by tectonics and paleogeography. The fan delta and nearshore subaqueous fan facies predominantly occur in the southern steep slope r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Climate change, which influences material supply, is the most decisive factor causing the occurrence of coal and oil shale. Characteristics and minerogenetic conditions Yilan Basin (Liu, 2007;Liu et al, 2012;Zhang et al, 2006) Fushun Basin Wang et al, 2001Wang et al, , 2007Xu et al, 2006) Huangxian Basin (Hou et al, 2006;Liu, 2008;Liu et al, 2009b;Xu et al, 2012) Jinbaotun Basin (Feng et al, 2015) Interbedded (2) The symbiosis mechanism of formations combining coal and oil shale is more complex and variable than of the mechanism of the formation of a single energy mineral resource. For symbiotic combinations of two important energy and mineral resources to occur, coexisting in the same basin, there must be several unique factors, such as peat accumulation, shale ore-forming material formation, suitable geological background, symbiotic mode and interdependent mechanisms, as discussed in this paper.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Climate change, which influences material supply, is the most decisive factor causing the occurrence of coal and oil shale. Characteristics and minerogenetic conditions Yilan Basin (Liu, 2007;Liu et al, 2012;Zhang et al, 2006) Fushun Basin Wang et al, 2001Wang et al, , 2007Xu et al, 2006) Huangxian Basin (Hou et al, 2006;Liu, 2008;Liu et al, 2009b;Xu et al, 2012) Jinbaotun Basin (Feng et al, 2015) Interbedded (2) The symbiosis mechanism of formations combining coal and oil shale is more complex and variable than of the mechanism of the formation of a single energy mineral resource. For symbiotic combinations of two important energy and mineral resources to occur, coexisting in the same basin, there must be several unique factors, such as peat accumulation, shale ore-forming material formation, suitable geological background, symbiotic mode and interdependent mechanisms, as discussed in this paper.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The comprehensive stratigraphic column since the Mesozoic in Gaoyou Depression, Subei Basin (integrated and modified from Zhang et al, 2016;Li et al, 2021) during the field investigations and production data from hydrocarbon exploitation. In the second step, fault seal evaluation is carried out regarding juxtaposition seal, fault rock seal, and cementation seal within study area, which is demonstrated by case studies.…”
Section: Database and Methodsmentioning
confidence: 99%
“…Location of Subei Basin in China; TR, Tarim Basin; JG, Junggar Basin; SC, Sichuan Basin; OD, Ordos Basin; EL, Erlian Basin; BB, Bohai Bay Basin; SL, Songliao Basin; integrated and modified from Liu et al, 2018, Liu, Yang, et al, 2020, Liu, Lai, et al, 2020 Location and distribution of structural units of Subei Basin; integrated and modified from Zhou et al, 2018; Distribution of structural units in and around Gaoyou Depression and datasets used; integrated and modified from Liu, Chen, et al, 2017Liu, He, et al, 2021, Liu, Jiang, et al, 2021, Liu, Jin, et al, 2021 seismic interpretation showing structural framework, integrated and modified from Zhang et al, 2016 Cretaceous which overlies unconformably on Palaeozoic carbonate sedimentary rocks (Li et al, 2012;Liu, 2009). The Cretaceous is predominantly composed of the Upper Cretaceous (Taizhou Formation, Chishan Formation, and Pukou Formation) and Lower Cretaceous (Gecun Formation) (Figure 2).…”
Section: Geological Settingsmentioning
confidence: 99%
See 2 more Smart Citations